2004
DOI: 10.1099/vir.0.79830-0
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of the respiratory syncytial virus P–P and P–N protein complexes and localization of the P protein oligomerization domain

Abstract: The RNA-dependent RNA polymerase complex of respiratory syncytial virus (RSV) is composed of the large polymerase (L), the phosphoprotein (P), the nucleocapsid protein (N) and the co-factors M2-1 and M2-2. The P protein plays a central role within the replicase-transcriptase machinery, forming homo-oligomers and complexes with N and L. In order to study P-P and N-P complexes, and the role of P phosphorylation in these interactions, the human RSV P and N proteins were expressed in E. coli as His-tagged or GST-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
110
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 29 publications
4
110
0
6
Order By: Relevance
“…Similarly to other paramyxoviruses (46)(47)(48), the hRSV phosphoprotein (P) could work as a chaperone to keep a pool of soluble monomeric N protein that does not bind to RNA (49). Such a pool of monomeric N molecules could be available either for nucleocapsid assembly or membrane binding and targeting to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other paramyxoviruses (46)(47)(48), the hRSV phosphoprotein (P) could work as a chaperone to keep a pool of soluble monomeric N protein that does not bind to RNA (49). Such a pool of monomeric N molecules could be available either for nucleocapsid assembly or membrane binding and targeting to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Human RSV P (strain Long) is phosphorylated mainly at S232 (7,8), although other minor phosphorylation sites have been identified (S30, S39, S45, T46, S54, T108, S116, S117, S119, S237) (9,10). The precise role of phosphorylation for P activity remains unclear, since (i) unphosphorylated P is competent for oligomerization and binding to N-RNA (11,12) and (ii) substitution of all the phosphorylated residues has little effect on viral transcription and replication (13,14). However, P phosphorylation could play a role in NC encapsidation in viral particles (10,13).…”
mentioning
confidence: 99%
“…Although there is no sequence similarity between the P proteins of Pneumovirinae and other related families and subfamilies in the Mononegavirales order, all share similar organization, structure, and functions. RSV P forms homotetramers of elongated shape and has a modular organization with a protease-resistant central domain containing a predicted coiled coil (aa 120 to 160) involved in oligomerization, flanked by two intrinsically disordered regions (aa 1 to 120 and 161 to 241) (11,(15)(16)(17). The C-terminal region of P (aa 231 to 241) is involved in the interaction with the NC (12,18).…”
mentioning
confidence: 99%
“…Previous data characterized in vitro an oligomerization domain in P protein central region and indicated that P oligomers could also occur in HRSV infected cells (2,9,10).…”
Section: Discussionmentioning
confidence: 99%